Pembangunan Toilet Sehat Untuk Meningkatkan Akses Sanitasi Yang Layak Di Mushola Al Barokah Desa Tenjo - Putri, Pratiwi Setyaning; Devita Mayasari; Budi Wicaksono; Tommy Iduwin; Tri Yuhanah; Sajiharjo; Wisnu Hariyanto (TERANG, 2024)
The Al-Barokah prayer room, which is located in Leuweung Gede Village, Tenjo Village, Tenjo District, Bogor Regency, is one of the religious infrastructures where comfortable toilets and adequate septic tank drainage are not available. Prayer rooms that do not have toilet facilities cause people who worship to have to walk long distances to throw away their waste or even throw their waste carelessly, causing the surrounding environment to become polluted. Through Community Service (PKM) activities with the theme Building Healthy Toilets and Septic Tanks at the Al-Barokah Prayer Room, the aim is to create a healthy and Open Defaction Free (ODF) environment or stop open defecation in Tenjo Village through the construction of toilet and septic tank infrastructure. at the AL-Barokah prayer room. The activity implementation method consists of 1) Survey to Tenjo Village; 2) Discussion with village officials; 3) Make a cost budget plan and toilet and septic tank design; 4) Purchase of building materials and implementation of construction; 5) Handover with village cadres. It is hoped that the toilet and septic tank construction activities able to increase the comfort of worship and reduce environmental pollution in Tenjo Village, especially in Leuweung Gede Village.